2020
DOI: 10.1111/bjh.16856
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 in bone marrow transplant recipients: reflecting on a single centre experience

Abstract: Coronavirus disease 2019 (COVID-19) is caused by the novel SARS-CoV-2 virus and has been declared a pandemic on the 9th of March by the WHO. A hallmark of COVID-19 management is supportive care and there is still no convincing evidence for a treatment which will reduce mortality. Severe COVID-19-associated sepsis characterized by acute respiratory distress syndrome (ARDS), secondary bacterial pneumonias, thrombotic complications, myocarditis, and gastrointestinal involvement are more prevalent in those with co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
85
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(90 citation statements)
references
References 10 publications
2
85
1
1
Order By: Relevance
“…Similarly, data for P-CA patients showed 51•5% patients (n=565 with leukocyte indices reported) having an ALC<1,000 cells/μL. While not reported in a manner permitting calculation of interquartile ranges, six HCT studies 92 , 94 , 99 , 100 , 101 reported ALC data with only one 101 showing a median ALC above the lymphopenia range.
Figure 3 Leukocyte indices of SOT recipients and A-CA patients with COVID-19.
…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Similarly, data for P-CA patients showed 51•5% patients (n=565 with leukocyte indices reported) having an ALC<1,000 cells/μL. While not reported in a manner permitting calculation of interquartile ranges, six HCT studies 92 , 94 , 99 , 100 , 101 reported ALC data with only one 101 showing a median ALC above the lymphopenia range.
Figure 3 Leukocyte indices of SOT recipients and A-CA patients with COVID-19.
…”
Section: Resultsmentioning
confidence: 96%
“…To be included, the study must have reported clinical data on adult (A-CA) or pediatric (P-CA) cancer patients and SOT or HCT recipients with confirmed COVID-19. Our inclusion and exclusion criteria identified 64 SOT studies, 11 HCT studies, [91][92][93][94][95][96][97][98][99][100][101] 25 A-CA studies, and one global P-CA database, 127 the COVID-19 and Childhood Cancer Registry (CCCR) ( Fig. 1 )(Supplemental Table 1).…”
Section: Search Strategy and Selection Criteriamentioning
confidence: 99%
“…Preliminary reports suggest that patients with an underlying malignancy have inferior outcomes. [3][4][5][6][7] While haematology patients are thought to be at increased risk of developing severe complications both due to immune dysfunction from their underlying haematological disorder and immunosuppressive therapies used for treatment, [8][9][10] delays in treatment of the underling malignancy may compromise patient safety and survival. Data from other cohorts worldwide suggest mortality from COVID-19 is higher in haematology patients compared to the general population, 3,11,12 with reported mortality rates between 39% and 50% in other British haematology patient cohorts.…”
mentioning
confidence: 99%
“…This practice can be a valid approach especially in services hosting highly immune-compromised patients such as those with acute leukemia and bone marrow transplant units. [ 14 ] Furthermore, cleaners in some health institutes live in shared residency places. [ 15 ] This may highlight the importance of extra-precautionary measures when appropriate such as regular COVID-19 testing in addition to housing spacing and rigorous measures for proper health and hand hygiene.…”
Section: Discussionmentioning
confidence: 99%